2012
DOI: 10.1128/aem.06965-11
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Mechanisms of Mycobacterium marinum Pathogenesis within the Environmental Amoeba Acanthamoeba castellanii

Abstract: bMycobacterium marinum is a waterborne mycobacterial pathogen. Due to their common niche, protozoa likely represent natural hosts for M. marinum. We demonstrate that the ESX-1 secretion system is required for M. marinum pathogenesis and that M. marinum utilizes actin-based motility in amoebae. Therefore, at least two virulence pathways used by M. marinum in macrophages are conserved during M. marinum infection of amoebae. Mycobacterial pathogens are responsible for some of the leading causes of death by infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 25 publications
3
50
0
1
Order By: Relevance
“…In their protozoan hosts, "hidden" mycobacteria might find easier opportunities to infect vertebrate end hosts, multiplying within protozoans to escape immune reactions (480). This ability to persist within amoebae has been widely documented (481)(482)(483). The internalization of infectious agents inside other parasites represents an evolutionary strategy for survival that may sometimes enhance pathogenesis or transmissibility (480).…”
Section: Interactions Between Actinobacteria and Invertebratesmentioning
confidence: 99%
“…In their protozoan hosts, "hidden" mycobacteria might find easier opportunities to infect vertebrate end hosts, multiplying within protozoans to escape immune reactions (480). This ability to persist within amoebae has been widely documented (481)(482)(483). The internalization of infectious agents inside other parasites represents an evolutionary strategy for survival that may sometimes enhance pathogenesis or transmissibility (480).…”
Section: Interactions Between Actinobacteria and Invertebratesmentioning
confidence: 99%
“…marinum infection of amoebae and macrophage-like cells. Acanthamoeba castellanii amoebae were cultured and maintained at room temperature in PYG-712 medium as previously described (40). M. marinum strains were cultured in vitro as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In M. marinum the extended RD1 locus (MMAR_5439 through MMAR_5459, based on homology to the genes in M. tuberculosis) is the only genomic region reported to be required for ESX-1 export (18,32,34,(36)(37)(38)(39). Transposon insertions within or targeted deletion of individual genes in the extended RD1 locus prevents the export of ESX-1 substrates, including EsxA (ESAT-6) and EsxB (CFP-10) (EsxA/B) in vitro and attenuates M. marinum in macrophage, amoeba, and zebrafish models of infection (32,40,41).In general, genetic manipulations to the ESX-1 system which result in loss of substrate secretion into the culture supernatant in vitro lead to loss of virulence in infection models (initially described in references 3 and 5). Recent work from Chen et al reported variants of EspA, an ESX-1 substrate in M. tuberculosis, which led to strains that were deficient for ESX-1 secretion as measured by Western blot analysis of culture filtrate proteins (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ESX-1 secretion system causes cytotoxicity in cell-based ex vivo models of infection, including macrophages and amoebae (12,27,30). Following lysis of the phagosomal membrane, the bacteria induce cytotoxicity, which leads to cell death.…”
Section: Assays For Measuring Esx-1 Secretion and Functionmentioning
confidence: 99%